Teknologi Asistif Bagi Pembelajaran Online Mahasiswa Berkebutuhan Khusus - Aldjon Nixon Dapa (Peneliti.net, 2022)
This study aims to describe the use of Assistive Technology for Online Learning for Students with Special Needs. The learning process at Manado State University since the Covid-19 pandemic has shifted to the network (Online). Distance learning that has taken place so far has not been without problems. For students with special needs, obstacles can be divided into general and special obstacles. Constraints generally can be in the form of network connections, internet costs and facilities to access information. Meanwhile, the special obstacle is Assistive Technology that suits their learning needs. The research method used is the development method. Where the research subject is Students with Special Needs at Unima Manado. From the results of the study it was found that the use of adaptive learning media with students with special needs was also still not optimal. Lecturers still think that if you have met in room zoom meetings, cisco webex, google meet, and other platforms for video conferencing, that is enough, even though students who are deaf have problems with audio if no one translates or helps with sign language, or students blind people who cannot see the visual display given by the lecturer. The process of using assistive technology in lectures has been carried out by lecturers, but with the characteristics of the learning abilities of students with special needs, it is necessary to provide assistance and guidance first, even after lectures, they still need to be continuously motivated.